2009
DOI: 10.1177/1049909109338355
|View full text |Cite
|
Sign up to set email alerts
|

Illness Awareness in Hospice: Application of a Semi-Structured Interview

Abstract: This study describes the results of a semi-structured interview to assess the illness awareness of cancer patients in Hospice. The results of this study are based on the interviews made in Rimini and Savignano sul Rubicone Hospices (n = 51). Psychologists evaluated illness awareness of the participants interviewed independently from the code system that is provided for the interview. According to the psychologists, 18 patients (35%) were aware, 11 patients (22%) were unaware, and 22 patients (43%) were aware w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…Likewise, Numico et al [12] found that among 649 cancer patients, although about three-quarters were aware of their diagnosis, knowledge about the palliative or curative aims of future treatments was evident in only half of the sample. This finding is in line with other Italian data showing that when the prognosis is unfavorable, the percentage of patients aware of their situation tends to decrease [13][14][15].…”
Section: Introductionsupporting
confidence: 92%
“…Likewise, Numico et al [12] found that among 649 cancer patients, although about three-quarters were aware of their diagnosis, knowledge about the palliative or curative aims of future treatments was evident in only half of the sample. This finding is in line with other Italian data showing that when the prognosis is unfavorable, the percentage of patients aware of their situation tends to decrease [13][14][15].…”
Section: Introductionsupporting
confidence: 92%
“…Awareness studies published between 1994 and 2009 showed that a trend of partial and non disclosure persisted [279], [280], [281], [282], [283], [284], [285], [286]. The choice of partial or non-disclosure arises within families, independently of patients’ requests [287].…”
Section: Resultsmentioning
confidence: 99%
“…However, although many patients acknowledge their approaching death, they may choose not to speak about it openly during their illness journey (Baider, 2008). Andruccioli et al (2009) explain that the patient may be so consumed with the intensity of his or her illness that he or she is unable to focus on anything else. Patients can also move back and forth from acknowledging to denying their approaching death due to recurring changes in their cognitive status, intensity of their illness (Andruccioli et al, 2009), or choosing to use The established ways of communication within a family group will largely be maintained following the diagnosis of a life-limiting illness.…”
Section: • Open Awareness • Suspicion Awareness • Mutual Awareness • mentioning
confidence: 99%
“…Andruccioli et al (2009) explain that the patient may be so consumed with the intensity of his or her illness that he or she is unable to focus on anything else. Patients can also move back and forth from acknowledging to denying their approaching death due to recurring changes in their cognitive status, intensity of their illness (Andruccioli et al, 2009), or choosing to use The established ways of communication within a family group will largely be maintained following the diagnosis of a life-limiting illness. These individual patterns of communication influence the way in which the patient will share his or her thoughts and wishes throughout his or her illness journey.…”
Section: • Open Awareness • Suspicion Awareness • Mutual Awareness • mentioning
confidence: 99%
See 1 more Smart Citation